"Potential carbon efficiency" as a new index to track the performance of biofuels production processes. (November 2020) - Poluzzi, Alessandro; Guandalini, Giulio; Romano, Matteo C.
Abstract: In a carbon constrained economy which targets a massive reduction of the CO2 emissions, biogenic carbon is bound to be a scarce resource with high economic value. In such scenario, the carbon efficiency may become the key performance index to represent the revenues of the biomass-to-X conversion plants. In this work, the potential carbon efficiency (PCE) indicator is defined to quantify the achievable carbon efficiency (i.e. the amount of carbon contained in the final product with respect to the available input carbon), of a stream or of a process unit. Compared to the conventional carbon efficiency (CE), that is affected only by the separation/addition of carbon-containing species, the PCE allows quantifying the potential variation of the achievable carbon efficiency in process units where no carbon separation occurs, but where a limiting element is added (e.g. hydrogen through steam addition) or oxygen content is increased (e.g. oxygen injection in a reformer). The difference between the CE and the PCE along a biomass conversion process is typically due to the excess of oxygen atoms in the syngas, which is removed as CO2 in the syngas conditioning unit. Therefore, the difference between CE and PCE shows the potential gain in carbon efficiency that can be obtained by the addition of H2 from an electrolysis process. In this paper, the PCE and the CE have been calculated along the process units of different biomass-to-X plants. The selected case studies allow comparing different gasification technologies (direct gasification, indirect gasification and sorption enhanced gasification) in plants for the production of methanol and synthetic natural gas, showing how CE and PCE are influenced by process units such as the gasification technology, syngas reforming, syngas conditioning and hydrogen addition. Highlights: New index "potential carbon efficiency" (PCE) defined and compared with conventional "carbon efficiency" (CE) index. PCE depends on presence of limiting elements and excess oxygen in the output stream of a certain process unit. PCE quantifies the variation of the achievable CE in units with no C separation. Direct gasification has higher gap between CE and PCE compared to indirect gasification along the process units. High gap between CE and PCE involves high benefits from integration with electrolysis.